IMPLEMENTATION OF BLUE OCEAN STRATEGY IN WINNING BUSINESS COMPETITION (CASE STUDY AT PT. TELKOM INDONESIA Tbk, WITEL SUKABUMI) - Aji Heryana Fasmala; Asep Muhamad Ramdan; Sopyan Saori (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Competition in the internet service industry in Indonesia has increased along with the demands and needs of the community. This is due to the development of technology that is increasingly advanced and rapid and raises the need to use the internet for every human activity. So there needs to be changes - changes in the right strategy to win business competition. This study aims to determine the Blue Ocean Strategy at PT. Telekomunikasi Indonesia Tbk, Witel Sukabumi in winning business competition. Informants in this study were Telkom Witel Sukabumi Strategy Manager, Strategy Manager Staff and HRD Staff Telkom Witel Sukabumi and Telkom Witel Sukabumi Customers. This study uses a qualitative method with a case study approach. Data collection techniques using observation, interviews and documentation. Technical data analysis through data reduction procedures, data presentation, and drawing or verifying conclusions. Data validation techniques in this study used source triangulation, technical triangulation and time triangulation. The results of the study show that Telkom is in a fairly tight competitive position but has the potential to move towards the blue ocean area, by using a blue ocean analysis framework, namely a four-step framework, a strategy canvas, and also implementing blue ocean principles will show that telkom witel sukabumi won business competition in fiber optic internet.